Migraine headache and labor market outcomes - Daniel I. Rees; Joseph J. Sabia (Institute for the Study of Labor (IZA), 2012)
While migraine headache can be physically debilitating, no study has attempted to estimate its effects on labor market outcomes. Using data drawn from the National Longitudinal Study of Adolescent Health, we estimate the effect of migraine headache on labor force participation, hours worked, and wages. We find that migraine headache is associated with a decrease in wages. However, there is little evidence that migraine headache leads to reductions in labor force participation or hours worked. We conclude that estimates of the cost of migraine headache to society should include its impact on wages.
Keywords: I10; J30; 330; migraine headache; wages; labor force participation; productivity; Psychische Störung; Lohn; Erwerbstätigkeit; Arbeitszeit; Schätzung; USA